Gestão de ativos intangíveis sob o enfoque da análise de rede de valor: Um estudo da rede universidade-sociedade - Klein, Simone Boruck (2021)
The research theme refers to the management of intangible assets from a network perspective, which used value network analysis (VNA) or value network analysis (Allee, 2008). Developed with the objective of analyzing the participation of intangible assets in the generation of value in the University-Society network. To that end, theoretical topics related to intangible assets were discussed, focusing on valuation models, manageable aspects and the generation of value. In the second part of the theorists, the historical evolution of the universities, the concept of the entrepreneurial university and the third current of activities of the university, or third mission, were listed. This study is justified in the face of the challenges of knowledge management, know how, organizational and personnel skills and innovates when using a network value analysis model, as it corresponds to an opportunity to develop paths towards knowledge as value creation occurs in universities. The university-society relationship, presented as the basis for this research, is also a relevant topic, given that, it seeks to provide a way of managing intangibles, in which it is intended to observe the fundamental value generation agents in Universities regarding their relationship with the local society. This relationship can be better explored in a technical focus as well as providing models for the construction of activities that foster the relationship under study. A case study was used, with a focus on analysis in the UTFPR Directorate of Business and Community Relations (DIREC), campus Santa Helena, PR. It is a university with a vocation to fulfill the mission of promoting the university-society relationship in a more active way. The choice of campuses was due to the characteristic of the small city and the short time the campus was opened in view of the construction already reached in the region. Data collection occurred through identification, questionnaire and document analysis. Data analysis uses content analysis by Bardin (1991) and value analysis by Alle (2008). The seven value conversion team results that are the departments that make up DIREC plus society. The mapping of value exchanges for the formation of intangible assets occurred by actions and activities developed by DIREC. From these, the elements of value creation of the university-society network emerge at UTFPR in Santa Helena, PR. The value network analysis (VNA) allows an efficient management of intangible assets already developed in the network and presents loopholes that can be developed for better use of the network, as it demonstrates the weak points of the analyzed network. Analyzes of the impact of the perceived value at UTFPR university were also carried out regarding the objectives of the university's third mission. It was noticed that the indicators of the dimension of human capital dissipated a perceived value greater than the other dimensions in the university-society network.